(untitled) (The Conference Hub, 2026)
This article analyzes the pedagogical significance of digital and innovative approaches in teaching the history of Uzbekistan. Within the scope of the study, the role of modern information and communication technologies, interactive and problem-based teaching methods in history education is examined, as well as their impact on increasing students’ cognitive activity and improving the quality of education. In addition, the possibilities of fostering historical thinking, critical reasoning, and national consciousness through innovative approaches are scientifically substantiated. The article also reveals the methodological aspects, advantages, and practical effectiveness of applying innovative technologies in history education.